2020
DOI: 10.1007/s00256-020-03484-y
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided muscle biopsy: a practical alternative for investigation of myopathy

Abstract: Objective We propose the use of ultrasound-guided muscle biopsy as a viable method of obtaining muscle specimen to aid the diagnosis of myopathy. We retrospectively review the diagnostic accuracy and patient feedback of ultrasound-guided muscle biopsies in our neuromuscular service. Method Multidisciplinary team meeting reviewed select patients and agreed on those suitable for ultrasound-guided muscle biopsy. They then underwent biopsy using direct ultrasound guidance and a modified Bergström needle. The spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Inclusion of MRI as part of the diagnostic evaluation for idiopathic inflammatory myopathies showed that sampling a muscle of intense T2‐weighted signal reduced the false negative biopsy rate to 0.19 compared with the overall cohort false negative biopsy rate of 0.23 [ 23 ]. One small study suggested a 100% diagnostic yield of biopsies from sites selected by positive MRI and additional targeting of biopsy site using US at the time of the procedure [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Inclusion of MRI as part of the diagnostic evaluation for idiopathic inflammatory myopathies showed that sampling a muscle of intense T2‐weighted signal reduced the false negative biopsy rate to 0.19 compared with the overall cohort false negative biopsy rate of 0.23 [ 23 ]. One small study suggested a 100% diagnostic yield of biopsies from sites selected by positive MRI and additional targeting of biopsy site using US at the time of the procedure [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…The tissue obtained through a needle biopsy is processed and examined histologically, and can also be used for biochemical and molecular studies [ 155 ]. For increased accuracy and safety, ultrasound guidance, as previously mentioned, can be employed during needle biopsies [ 156 ]. Ultrasound allows for real-time visualization of the muscle, helping to precisely target the area of interest, which minimizes the risk of complications and increases the diagnostic yield.…”
Section: Emerging Biopsy Techniquesmentioning
confidence: 99%